Factors Affecting the Quality of Life of Older People during the COVID-19 Pandemic - Mei Rianita Elfrida Sinaga; Susi Roida Simanjuntak; Rozzano C. Locsin (Department of Nursing, Faculty of Medicine, Diponegoro University, 2022)
Background: Changes that occur in the life of older people during the COVID-19 pandemic present many challenges towards achieving better quality of life However, only a limited number of studies that evaluate factors affecting the quality of life of older people during the COVID-19 pandemic are available.Purpose: This study aimed to identify the quality of life and factors affecting the quality of life of older people during the COVID-19 pandemic.Methods: This study employed a cross-sectional design using anonymous online questionnaires of 208 respondents who were selected using purposive sampling. This study was conducted during September to December 2020 in North Sumatra and Yogyakarta provinces. The QoL was measured using the World Health Organization Quality of Life (WHOQOL)-BREF questionnaire in the Indonesian version. The descriptive statistics were calculated for socio-demographics, while their association with quality of life was analyzed using Mann-Whitney and Kruskal-Wallis statistics. Multiple linear regression was used to determine the predictor factors affecting the quality of life of older people.Results: The results of the study showed that the mean and standard deviation for physical domain factors was 64.46(11.81); 64.61(11.98) for the psychological domain; 64.85(12.81) for the social domain, and 61.08(13.01) for the environmental domain. Factors significantly associated with the quality of life included age, retirement, living situation, health insurance, and medical history (p<0.05). However, the predictor factor affecting the quality of life of older people during the COVID-19 pandemic was medical history (β-value=0.25).Conclusion: Predictor factor affected the quality of life was medical history. The study suggests the government and health care professionals, specifically community health nurses, to promote the utilization of Integrated Elderly Health Service (IEHS) among older adults and families to maintain the quality of health.